COUNSELING AND SCREENING FOR RISK FACTORS FOR HYPERTENSION IN CLASS IIA WOMEN'S CORRECTIONAL INSTITUTIONS IN BANDAR LAMPUNG CITY IN 2024 - Aryawati, Wayan; Sari, Fitri Eka; Pratama, Gilang Raka; Risdinar, Risa Rismaya; Setya P., Kevin Andhara (LPPM Univ. Ibn Khaldun Bogor, 2024)
The prevalence of hypertension in individuals over 18 years of age and diagnosed by a health professional reaches 9.4%. In addition, around 9.5% of the population takes medication to treat hypertension. Therefore, there are around 0.1% of the population who take hypertension medication even though they have never been officially diagnosed by a health professional. The prevalence of hypertension in Indonesia, measured in individuals over 18 years of age, reached 34.11%. The aim of this service is to carry out health screening and counseling to increase the knowledge of the inmates regarding hypertension. The service method is carrying out health screening such as checking blood pressure, weight, height and BMI then carrying out outreach activities related to preventing hypertension. The service was carried out on January 19 2024 with a sample size of 235 inmates. at the Class IIA Women's Correctional Institution in Bandar Lampung City. The results of the service that had been carried out were concluded that 76.6% of the inmates had good knowledge and 23.4% had poor knowledge. Those with normal blood pressure were 74.6% and those with high blood pressure were 26.0%. 26.0% of their families had a history of hypertension and 74.6% did not have a history of hypertension. Those who had a sleep pattern of <6 hours a day were 8.10% and those who did not have a sleep pattern of >6 hours a day were 91.9%. It is hoped that health workers can continue to improve health education and education regarding NCDs, especially hypertension.